2017
DOI: 10.1080/02699206.2017.1306110
|View full text |Cite
|
Sign up to set email alerts
|

Validation and norming of the Intelligibility in Context Scale in Northern Viet Nam

Abstract: Vietnamese is one of the 20 most commonly spoken languages in the world; however, there are no standardised tools to assess Vietnamese children's speech. This study aimed to validate and norm the Vietnamese version of the Intelligibility in Context Scale (ICS-VN). Data were collected from parents of 181 children (aged 2;0-5;11) living in Ha Noi, Northern Viet Nam. The mean ICS-VN score was 4.43 (out of a maximum of 5), indicating that children were 'usually' to 'always' intelligible; however, item-level scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
3
27
1
Order By: Relevance
“…Again, higher cut-offs increase specificity, but sensitivity is appreciably compromised. +LRs only showed a ''small increase in the likelihood'' (OMERAD, 2008) of SD at the cut-off ''some difficulty'', but show ''large and conclusive'' increases in the likelihood of SD at the cut-off ''a lot of difficulty''. -LRs for teacher responses were more conclusive at the level of ''some difficulty'' but only when ''outside the classroom'' is utilised.…”
Section: Cross Tabulation Of the Cfm Results By The Ics Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Again, higher cut-offs increase specificity, but sensitivity is appreciably compromised. +LRs only showed a ''small increase in the likelihood'' (OMERAD, 2008) of SD at the cut-off ''some difficulty'', but show ''large and conclusive'' increases in the likelihood of SD at the cut-off ''a lot of difficulty''. -LRs for teacher responses were more conclusive at the level of ''some difficulty'' but only when ''outside the classroom'' is utilised.…”
Section: Cross Tabulation Of the Cfm Results By The Ics Resultsmentioning
confidence: 91%
“…Higher cut-offs increase specificity but sensitivity is compromised considerably. The cut-offs ''a lot of difficulty'' and ''cannot do at all'' showed positive likelihood ratios (+LR) ranging from 64.2 to 116.3 indicating ''large and conclusive'' (OMERAD, 2008) results, however confidence intervals were very wide. Parent responses for ''inside'' show less convincing + LR, but still conclusive at 12.8 at the cut-off ''some difficulty'' with much narrower confidence intervals.…”
Section: Cross Tabulation Of the Cfm Results By The Ics Resultsmentioning
confidence: 99%
“…Significant correlations were found between children's ICS scores and age (e.g., McLeod et al, 2015;Neumann et al, 2017;Phạm et al, 2017). Some studies showed no significant difference between children's ICS scores and sex (Phạm et al, 2017);whereas, in McLeod et al (2015) females were rated significantly higher than males (p < .005) with no significant interaction between sex and age. There was no significant difference in ICS scores between participants who spoke one or more than one language .…”
Section: Comparisons Between Groupsmentioning
confidence: 95%
“…Some studies showed low but significant correlations with SES (Neumann et al, 2017); whereas, others did not . In Vietnam, Phạm et al (2017) demonstrated significant factors influencing ICS scores were parents' occupation level and mothers' (but not fathers') education level.…”
Section: Comparisons Between Groupsmentioning
confidence: 96%
“…It assesses intelligibility and comprehensibility, which are comparable constructs to CFM questions on difficulty being understood when speaking. The ICS had already been rigorously translated into Fijian and Fiji-Hindi and has been widely used both with children with speech sound disorders [31,58] and with typically developing speech [32,58,59]. For our study, case definition for speech difficulties were ICS scores: 1.8 to <2.5 (moderate) and 1.0 to <1.8 (severe). Cognitive impairment was assessed using the Cambridge Neuropsychological Test Automated Battery (CANTAB) [32] and cases included subjects with CANTAB Overall Impairment Scores of 3 (moderate) and 4–5 (severe).…”
mentioning
confidence: 99%